2015
DOI: 10.1111/sum.12168
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effect of biochar size and organic amendments on methane consumption in a tropical vertisol

Abstract: Biochar (BC) application to agricultural soil has been proposed as an effective countermeasure to mitigate climate change. A laboratory incubation experiment was carried out to gain insight into the effectiveness of BC on methane (CH4) consumption in a tropical clayey vertisol. Except for the control treatment, BC of two different sizes (<0.25 or 0.25–2.00 mm) was mixed with vermicompost (VC), poultry manure (PM) or farmyard manure (FYM). BC and organic amendment were added to soil at 10% w/w and 80 kg N/ha, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The number of studies using upland soils and measuring CH 4 consumption with/without biochar is currently not large. Kollah et al (2015) observed significantly increased CH 4 consumption rates in a lab study with tropical soil amended with biochar (with or without organic amendments), as did Karhu et al (2011) in in-field boreal, ploughed grassland soil. Karhu et al (2011) assumed that the observed doubling of the CH 4 consumption in the ploughed grassland soil was due to altered gas diffusivity and water holding capacity (which increased by 11%).…”
Section: Biochar Effects On Net Ch 4 Consumption In Oxic Upland Soilsmentioning
confidence: 75%
“…The number of studies using upland soils and measuring CH 4 consumption with/without biochar is currently not large. Kollah et al (2015) observed significantly increased CH 4 consumption rates in a lab study with tropical soil amended with biochar (with or without organic amendments), as did Karhu et al (2011) in in-field boreal, ploughed grassland soil. Karhu et al (2011) assumed that the observed doubling of the CH 4 consumption in the ploughed grassland soil was due to altered gas diffusivity and water holding capacity (which increased by 11%).…”
Section: Biochar Effects On Net Ch 4 Consumption In Oxic Upland Soilsmentioning
confidence: 75%
“…Result highlighted that organic farming can significantly decrease global atmospheric CH 4 budget in addition to improving soil physical and biological properties. Kollah et al, (2015) showed that biochar enhanced the methane consumption potential in tropical Vertisols, particularly smaller sized fractions (<0.25 mm), and could be an effective strategy to mitigate atmospheric CH 4 . Organic amendments like vermicompost and FYM were more effective than poultry manure in improving methane consumption in soils.…”
Section: Microbiology Of Climate Changementioning
confidence: 99%
“…Microcosms were prepared following the protocol as described elsewhere (Kollah et al ., 2015). Each microcosm was constituted of 130 ml vial with 20 g soil treated with chlorpyrifos as described below.…”
Section: Methodsmentioning
confidence: 99%